Risk factors for housing insecurity following bereavement: a cross-sectional analysis of UK survey respondents - C. R. L. Simpson-Greene; B. F. Hudson (Palliative Care and Social Practice)
Background: Housing insecurity can be linked to bereavement and is often caused or exacerbated by loss of household income and restrictions to some tenancy agreements. Housing insecurity can result in significant practical disruption, increase risk of adverse health outcomes and decrease quality of life. However, despite the impact of housing insecurity on experiences following bereavement, little is known about its underlying risk factors. Aim: To investigate characteristics associated with housing insecurity, defined as odds of having to move home following bereavement. Methods: This exploratory, cross-sectional analysis used data from an online survey commissioned by Marie Curie in November 2023. The survey investigated administrative difficulties faced by UK residents who had experienced a close bereavement in the past five years. Logistic regression modelling was used to quantify the strength and direction of the association between characteristics and odds of having to move home. Results: In all, 2901 bereaved people were included in the analysis. The incidence of having to move home following bereavement was 11.2% ( n  = 324). Characteristics associated with significantly increased odds of having to move in fully adjusted models included being younger, being male, renting privately, bereavement following the death of a younger person, being bereaved in the last 12 months and completing practical tasks following bereavement, a proxy measure for the relationship between the bereaved and deceased. Living in Wales, living in Scotland and living in Northern Ireland were each associated with significantly lower odds of having to move compared with living in England. Data on ethnicity or socioeconomic factors were unavailable. Conclusion: Certain groups of people may have an increased risk of having to move home following bereavement. This highlights inequity in experiences of bereavement and emphasises the need for research to explore other aspects of housing insecurity and the means to address potential inequities.